Phyllosphere Fungal Communities of Plum and Antifungal Activity of Indigenous Phenazine-Producing Pseudomonas synxantha Against Monilinia laxa - Janakiev, Tamara; Dimkić, Ivica; Unković, Nikola; Ljaljević Grbić, Milica; Opsenica, Dejan; Gašić, Uroš; Stanković, Slaviša; Berić, Tanja (Frontiers in Microbiology, 2019)
European plum (Prunus domestica L.) is a significant commercial crop in Serbia in terms of total fruit production, and it is traditionally processed into slivovitz brandy. The annual plum yields in Serbia is strongly affected by Monilinia laxa, causing brown rot in stone fruits. The fungal communities associated with leaves and fruits of four local Serbian plum cultivars (Požegača, Ranka, Lepotica and Rodna) were investigated in two phenological stages during early (May) and late (July) fruit maturation. Alpha diversity indices showed that fungal communities were heterogeneous and Beta diversity indicated that autochthonous fungal communities depended upon seasonal changes and the cultivars themselves. The phylum Ascomycota was the most abundant in all samples, with relative abundance (RA) between 46% in the Požegača cultivar (May) and 89% in the Lepotica cultivar (July). The most abundant genus for all plum cultivars in May was Aureobasidium, with RA from 19.27 to 33.69%, followed by Cryptococcus, with 4.8 to 48.80%. In July, besides Cryptococcus, different genera (Metschnikowia, Fusarium and Hanseniaspora) were dominant on particular cultivars. Among all cultivable fungi, molecular identification of 11 M. laxa isolates from four plum cultivars was performed simultaneously. Bacterial isolates from the plum phyllosphere were tested for their potential antifungal activity against indigenous M. laxa isolates. The most potent antagonist, P4/16_1 was identified as Pseudomonas synxantha, which reduced mycelial growth of M. laxa from 80 to 87.5%. The production of volatile organic compounds was observed as well. Screening for the antibiotic coding gene was positive for phenazine-1-carboxylic acid, and benzene extraction of P. synxantha-active compounds was done. The crude benzene extract exhibited 57–63% inhibition of mycelial growth. The conducted LC/MS analysis of the crude extract confirmed the presence of phenazine derivatives amongst other compounds. Scanning electron microscopy revealed morpho-physiological changes in the hyphae of M. laxa isolates caused by the cell culture and the P. synxantha P4/16_1 crude benzene extract. This is first report of antagonistic activity of P. synxantha against M. laxa induced by diffusible and volatile antifungal compounds, and it appears to be a promising candidate for use as a biocontrol agent against brown rot-causing fungi.